Conventional Cold steel and Modern technique BiZact LigaSure for tonsillectomy: A comparative analysis - Muhammad Saleem, Ashar Alamgir, Syeda Jamila Ali, Hafiz Sajjad Hyder, Sarwat Bibi, Sumara Tabassum, Muhammad Saleem, Ashar Alamgir, Syeda Jamila Ali, Hafiz Sajjad Hyder, Sarwat Bibi, Sumara Tabassum (Journal of Rawalpindi Medical College, 2022)
Background & Objective: One of the bulk number of operations carried out at otorhinolaryngology department across globe is Tonsillectomy. With the advent of refined surgical tools along with surgical approaches, the conventional methods are now taken over by these new interventions. The study aims to explore the use and advantages of BiZact LigaSure tonsillectomy as compared to the old conventional method. Material & Methods: A comparative study was conducted using non-probability purposive sampling technique at Aziz Fatimah Hospital, Faisalabad. 100 participants were divided in two groups. Group A (50 patients) underwent BiZact LigaSure tonsillectomy and Group B (50 patients) with conventional cold steel method. Per-operative variables such as Blood loss and Operative time and Post-operative variable such as Pain was assessed. The data was analyzed in SPSS 20 using independent t- test. Results: The mean age in group A and B was 12, 12 respectively. The blood loss calculated in Group A patients undergoing BiZact LigaSure tonsillectomy was 0.390.15 ml and in Group B 15.92.65 ml. The mean operation time in group A and B was calculated as 4.260.66 and 32.385.56. Both of these variables were recorded as highly significant as the P value = 0.000. Pain was assessed using the VAS pain scale. Post-operative pain variable was also recorded as highly significant variable. Conclusion: The study concludes that BiZact ligaSure tonsillectomy is more effective and safe procedure than the conventional cold steel method. This new intervention significantly reduces the blood loss during surgeries, operative time and post-operative pain.